2007
DOI: 10.1161/01.atv.0000252790.70572.0c
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride:High-Density Lipoprotein Cholesterol Effects in Healthy Subjects Administered a Peroxisome Proliferator Activated Receptor δ Agonist

Abstract: Objectives-Exercise increases fatty acid oxidation (FAO), improves serum high density lipoprotein cholesterol (HDLc) and triglycerides (TG), and upregulates skeletal muscle peroxisome proliferator activated receptor (PPAR)␦ expression. In parallel, PPAR␦ agonist-upregulated FAO would induce fatty-acid uptake (via peripheral lipolysis), and influence HDLc and TG-rich lipoprotein particle metabolism, as suggested in preclinical models. Methods and Results-Healthy volunteers were allocated placebo (nϭ6) or PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
141
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(156 citation statements)
references
References 49 publications
9
141
1
5
Order By: Relevance
“…There was also a striking reduction of fasting plasma NEFA, which was seen in the context of increased relative incorporation of labeled CO 2 originating from the fat content in the experimental meal, suggesting increased fat oxidation. The pattern of change in mRNA content in skeletal muscle suggested that pathways for fat oxidation, in both fast and slow fiber types, were specifically upregulated in response to the PPAR␦ drug, which is in line with observations from studies in rodents and human cells (32). Importantly, the increased fat oxidation was seen without any signs of deterioration of glucose/insulin homeostasis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was also a striking reduction of fasting plasma NEFA, which was seen in the context of increased relative incorporation of labeled CO 2 originating from the fat content in the experimental meal, suggesting increased fat oxidation. The pattern of change in mRNA content in skeletal muscle suggested that pathways for fat oxidation, in both fast and slow fiber types, were specifically upregulated in response to the PPAR␦ drug, which is in line with observations from studies in rodents and human cells (32). Importantly, the increased fat oxidation was seen without any signs of deterioration of glucose/insulin homeostasis.…”
Section: Discussionsupporting
confidence: 85%
“…PPAR␦ knockout mice appear to be insulin resistant (31). A recent report showed that GW501516 given to lean healthy subjects during metabolic ward conditions for 2 weeks resulted in a modest lowering of diurnal triglyceride concentrations and a lesser lowering of HDL cholesterol concentrations than in controls (32).…”
mentioning
confidence: 99%
“…by guest, on May 12, 2018 www.jlr.org Downloaded from accelerated RCT, is not confi ned to mice but has also been demonstrated to occur in primates and humans ( 18,19 ). Here, we show that the effect of PPAR ␦ on neutral sterol excretion is in part mediated by stimulation of TICE.…”
Section: Resultsmentioning
confidence: 61%
“…Subsequent cholesterol and apolipoprotein analysis of the lipoprotein profi les in FVB mice revealed a shift from HDL to LDL in both GW610742-treated groups. In contrast, earlier studies in monkeys and humans reported increased HDL cholesterol levels upon PPAR ␦ activation ( 18,19 ). Also in DBA1 mice, PPAR ␦ activation resulted in higher HDL levels ( 20 ).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation